THE ASSESSMENT OF CONTAMINATION AND SOURCE OF POLYCYCLIC AROMATIC HYDROCARBONS FROM THE SEDIMENTS OF THE SOMEȘ RIVER - PĂNESCU, Vlad; HERGHELEGIU, Mihaela Cătălina; POP, Sorin; ANTON, Mircea; BELDEAN-GALEA, Mihail Simion (Studia Universitatis Babeș-Bolyai Ambientum, 2022)
Polycyclic aromatic hydrocarbons (PAHs) represent an important class of environmental pollutants that are derived from both natural and anthropogenic sources. Due to their toxic, mutagenic, carcinogenic and bioaccumulation potential there are continuous concerns over the PAHs contents in the aquatic media. The aim of this work was to evaluate the distribution of PAHs in the sediments of Someș River, to assess their occurrence and to establish the origin (pyrogenic/petrogenic) of pollution sources. 13 sampling points were selected covering the distance from Cluj-Napoca to Satu Mare in order to assess the contribution of urban agglomeration over the concentration of PAHs in sediments. For the determination of the compounds GC-MS analyses were performed. PAH diagnostic ratios have been used as a tool for identifying and assessing the pollution emission sources. The obtained results showed that, the concentration of PAHs measured varied between 33.3 and 251.6 µg kg-1. Benzo[a]pyrene was found in most of the samples. A general tendency of higher concentration values on the exit point of the river from cities than from the entering point was found. The isomeric ratios indicated that most of the sources were of pyrogenic origin, rather than petrogenic. As expected, the concentrations of ƩPAHs were below the maximum accepted limit of 1 mg kg-1 regulated in Romania.